Molecular Characterization of Proton-Pumping NADH Family in Hydatids Isolated From Cattle: Karakterisasi Molekuler Keluarga NADH Pemompa Proton pada Hidatid yang Diisolasi dari Sapi - Challoob, Maysoon Khazail; AL-Asadi , Sarmad Awad Mozan (Universitas Muhammadiyah Sidoarjo, 2025)
Echinococcus granulosus mainly causes cystic echinococcosis and its energy from complex VI depends on NAD families. The study aimed to characterize and investigate these families in the E.granulosus G1 strain, as well as to genotype hydrophobic dehydrogenases. The results revealed the G1 strain has 21 subunits of proton-pumping NADH dehydrogenases distributed between the nuclear and mitochondrial genomes. Fifteen subunits (71.43%) were in the mitochondrial genome, and six subunits (28.57%) were in the nuclear genome. The hydrophobic NADI to NAD4L subunits were amplified using specifically designed primers and were 100% present in the protoscoleces and germinal layers of hydatids. They had 98.1-100% identities with their counterparts from the reference G1 strain. Phylogeny showed that hydrophobic subunits clustered with their counterparts in the G1 strain and were distant from their counterparts in G6 and G7 strains. The hydrophobic subunits were conserved between the protoscoleces and germinal layer of hydatids, as well as between individuals of the G1 strain. Additionally, all proton-pumping NADH dehydrogenases can be used in the diagnosis of the closely related strains G1 and G3. Highlights: granulosus G1 Strain: 21 NADH dehydrogenase subunits identified. Gene Location: 71.43% mitochondrial, 28.57% nuclear genomes. Diagnostic Use: Hydrophobic subunits differentiate G1/G3 strains from G6/G7. Keywords: E. granulosus, G1 strain, NADH family, hydatids, hydrophobic